Acute Effect of Mitral Valve Repair on Mitral Valve Geometry - Noack, Thilo; Wittgen, Kathleen; Kiefer, Philipp; Emrich, Fabian; Raschpichler, Matthias; Eibel, Sarah; Holzhey, David; Misfeld, Martin; Mohr, Friedrich-Wilhelm; Borger, Michael; Ender, Joerg; Seeburger, Joerg (The Thoracic and Cardiovascular Surgeon, 2019)
Background The aim of this study was to quantify acute mitral valve (MV) geometry dynamic changes throughout the cardiac cycle using three-dimensional transesophageal echocardiography (3D TEE) in patients undergoing surgical MV repair (MVR) with ring annuloplasty and optional neochord implantation.Methods Twenty-nine patients (63 ± 10 years) with severe primary mitral regurgitation underwent surgical MVR using ring annuloplasty with or without neochord implantation. We recorded 3D TEE data throughout the cardiac cycle before and after MVR. Dynamic changes (4D) in the MV annulus geometry and anatomical MV orifice area (AMVOA) were measured using a novel semiautomated software (Auto Valve, Siemens Healthcare).Results MVR significantly reduces the anteroposterior diameter by up to 38% at end-systole (36.8–22.7 mm; p < 0.001) and the lateromedial diameter by up to 31% (42.7–30.3 mm; p < 0.001). Moreover, the annular circumference was reduced by up to 31% at end-systole (129.6–87.6 mm, p < 0.001), and the annular area was significantly decreased by up to 52% (12.8–5.7 cm2; p < 0.001). Finally, the AMVOA experienced the largest change, decreasing from 1.1 to 0.2 cm2 during systole (at midsystole; p < 0.001) and from 4.1 to 3.2 cm2 (p < 0.001) during diastole.Conclusions MVR reduces the annular dimension and the AMVOA, contributing to mitral competency, but the use of annuloplasty rings reduces annular contractility after the procedure. Surgeons can use 4D imaging technology to assess MV function dynamically, detecting the acute morphological changes of the mitral annulus and leaflets before and after the procedure.
Keywords: mitral valve repair; mitral regurgitation; mitral valve model; 3D echocardiography; mitral valve geometry